Water management across space and time in India - Farhat Naz; Saravanan V. Subramanian (University of Bonn, Center for Development Research (ZEF), 2010)
This paper attempts to give a spatial and temporal overview of water management in India. It traces how people and the successive regimes made choices across space and time from a wide range of water control and distribution technologies. The paper divides the water management in India into four periods: (i) the traditional system of water management before colonial times; (ii) response from the colonial rulers to manage the complex socio-ecological system; (iii) large scale surface water development after independence; and (iv) finally, the small-scale community and market-led revolution. Hence an attempt has been made to describe the water management over the four periods, which has transformed the irrigation and water management scenario in India. Moreover the paper shows how development of water management and its practices are linked with the social, religious, economic development with the rise and fall of the ruling regime. While these different periods attempts to manage water in different ways, the paper reveals a gap in research towards understanding the ability of community to integrate by default these diverse technologies to achieve their social goal of survival.
Keywords: 350; Water Management; Canal Revolution; Groundwater Governance; Watershed Management; Community-Based Water Management